Device Applications of Epitaxial III-Nitride Semiconductors - Shetty, Arjun (2018)
Through the history of mankind, novel materials have played a key role in techno- logical progress. As we approach the limits of scaling it becomes difficult to squeeze out any more extensions to Moore’s law by just reducing device feature sizes. It is important to look for an alternate semiconductor to silicon in order to continue making the progress predicted by Moore’s law. Among the various semiconductor options being explored world-wide, the III-nitride semiconductor material system has certain unique characteristics that make it one of the leading contenders. We explore the III-nitride semiconductor material system for the unique advantages that it offers over the other alternatives available to us. This thesis studies the device applications of epitaxial III-nitride films and nanos- tructures grown using plasma assisted molecular beam epitaxy (PAMBE) The material characterisation of the PAMBE grown epitaxial III-nitrides was car- ried out using techniques like high resolution X-ray diffraction (HR-XRD), field emis- sion scanning electron microscopy (FESEM), room temperature photoluminescence (PL) and transmission electron microscopy (TEM). The epitaxial III-nitrides were then further processed to fabricate devices like Schottky diodes, photodetectors and surface acoustic wave (SAW) devices. The electrical charcterisation of the fabricated devices was carried out using techniques like Hall measurement, IV and CV measure- ments on a DC probe station and S-parameter measurements on a vector network analyser connected to an RF probe station. We begin our work on Schottky diodes by explaining the motivation for adding an interfacial layer in a metal-semiconductor Schottky contact and how high-k di- electrics like HfO2 have been relatively unexplored in this application. We report the work carried out on the Pt/n-GaN metal-semiconductor (MS) Schottky and the Pt/HfO2/n-GaN metal-insulator-semiconductor (MIS) Schottky diode. We report an improvement in the diode parameters like barrier height (0.52 eV to 0.63 eV), ideality factor (2.1 to 1.3) and rectification ratio (35.9 to 98.9 @2V bias) after the introduction of 5 nm of HfO2 as the interfacial layer. Temperature dependent I-V measurements were done to gain a further understanding of the interface. We observe that the barrier height and ideality factor exhibit a temperature dependence. This was attributed to inhomogeneities at the interface and by assuming a Gaussian distribution of barrier heights. UV and IR photodetectors using III-nitrides are then studied. Our work on UV photodetectors describes the growth of epitaxial GaN films. Au nanoparticles were fabricated on these films using thermal evaporation and annealing. Al nanostruc- tures were fabricated using nanosphere lithography. Plasmonic enhancement using these metallic nanostructures was explored by fabricating metal-semiconductor-metal (MSM) photodetectors. We observed plasmonic enhancement of photocurrent in both cases. To obtain greater improvement, we etched down on the GaN film using reac tive ion etching (RIE). This resulted in further increase in photocurrent along with a reduction in dark current which was attributed to creation of new trap states. IR photodetectors studied in this thesis are InN quantum dots whose density can be controlled by varying the indium flux during growth. We observe that increase in InN quantum dot density results in increase in photocurrent and decrease in dark current in the fabricated IR photodetectors. We then explore the advantages that InGaN offers as a material that supports surface acoustic waves and fabricate InGaN based surface acoustic wave devices. We describe the growth of epitaxial In0.23 Ga0.77 N films on GaN template using molecular beam epitaxy. Material characterisation was carried out using HR-XRD, FESEM, PL and TEM. The composition was determined from HR-XRD and PL measurements and both results matched each other. This was followed by the fabrication of interdigited electrodes with finger spacing of 10 µm. S-parameter results showed a transmission peak at 104 MHz with an insertion loss of 19 dB. To the best of our knowledge, this is the first demonstration of an InGaN based SAW device. In summary, this thesis demonstrates the practical advantages of epitaxially grown film and nanostructured III-nitride materials such as GaN, InN and InGaN using plasma assisted molecular beam epitaxy for Schottky diodes, UV and IR photodetec- tors and surface acoustic wave devices.